Position of SGLT2i in prediabetes: A systematic review of literature - Kaushik Biswas; Vijaya Bhaskar Reddy; Krishna Seshadri; Nitin Kapoor; Mala Dharmalingam; Thamburaj Anthuvan (Journal of Diabetology)
Prediabetes, characterized by impaired fasting glucose and/or impaired glucose tolerance with HbA1c levels ranging from 5.7 to 6.4%, affects approximately 720 million individuals globally, including a significant proportion of the South-Asian population and adolescents. This condition, often preceding Type 2 diabetes mellitus (T2DM), poses elevated risks for cardiovascular and renal complications. Diet and lifestyle measures are currently recommended for prediabetes management, and pharmacologic therapeutic options for prediabetes are limited to metformin in selected patients. Sodium-glucose co-transporter-2 inhibitors (SGLT2i), a class of oral anti-glycemic agents, have emerged as potential therapeutic options for prediabetes management due to their multifaceted benefits, including reduction in progression to T2DM, weight reduction, and cardiorenal protection. This systematic review evaluates the efficacy and safety of SGLT2i in managing prediabetes, with or without complications. By performing a comprehensive search of randomized control trials and registry studies, our review includes 14 publications and 19 trials. Findings indicate that SGLT2i treatment is associated with improved glycemic parameters, delayed progression to diabetes, and reduced risks of micro and macrovascular complications, particularly among individuals with preexisting cardiorenal conditions. The review highlights the need for further studies to develop structured guidelines for the management of prediabetes using SGLT2i, potentially mitigating the global burden of this condition and its complications.